Correlates of protection for meningococcal surface protein vaccines: lessons from the past. (3rd June 2022) - Findlow, Jamie; Lucidarme, Jay; Taha, Muhamed-Kheir; Burman, Cynthia; Balmer, Paul
ABSTRACT: Introduction: Recombinant surface protein meningococcal serogroup B (MenB) vaccines are available but with different antigen compositions, leading to differences between vaccines in their immunogenicity and likely breadth of coverage. The serology and breadth of coverage assessment for MenB vaccines are multifaceted areas, and a comprehensive understanding of these complexities is required to appropriately compare licensed vaccines and those under development. Areas covered: In the first of two companion papers that comprehensively review the serology and breadth of coverage assessment for MenB vaccines, the history of early meningococcal vaccines is considered in this narrative review to identify transferable lessons applicable to the currently licensed MenB vaccines and those under development, as well as their serology. Expert opinion: Understanding correlates of protection and the breadth of coverage assessment for meningococcal surface protein vaccines is significantly more complex than that for capsular polysaccharide vaccines. Determination and understanding of the breadth of coverage of surface protein vaccines are clinically important and unique to each vaccine formulation. It is essential to estimate the proportion of MenB cases that are preventable by a specific vaccine to assess its overall potential impact and to compare the benefits and limitations of different vaccines in preventing invasive meningococcal disease.